STUDIES ON THE TOXICITY OF COPPER, ZINC AND COPPER-ZINC MIXTURE ON CIRRHINA MRIGALA (HAMILTION) - SITHANAND, T.; DAS, S. SAM MANOHAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
The toxicity of copper, zinc and copper-zinc mixtures on Cirrhina mrigala was investigated. Copper was more toxic compared to zinc. In mixtures, copper enhanced the toxicity of zinc and zinc moderated the toxicity of copper.